THE EFFECTS OF STEM HEIGHT ON THE PHYSICAL PROPERTIES OF EUROPEAN LARCH (Larix decidua Mill.) WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this study was to determine the effect of stem height on the physical properties of European larch (Larix decidua Mill.) wood. The sample trees harvested from Maçka Research Forest in Trabzon. The preparation of small clear specimens and application of test procedures were performed according to Turkish standards. Wood density (oven dry and in 12 % moisture content), basic density, shrinkage and swelling values, were determined for physical properties of wood. Moreover the variation of these properties were determined related to stem height. Consequently, the decreasing trend in the physical properties was observed in direction from bottom to top.